Evaluation of Shear-Flexure Interaction Behavior of Reinforced Concrete Wall - Jimmy Chandra; Gata Milla; Jonathan Aurelius Tambuna (Institute of Research and Community Outreach - Petra Christian University, 2024)
Reinforced concrete (RC) wall is a critical structural member that resists lateral loadings, such as earthquake and wind. RC wall having moderate height to length ratio, 1.50-2.50, has the altered shear-flexure interaction (SFI) behavior, so shear and flexural failure mechanisms occur almost concurrently. Therefore, an experimental study of a moderate RC wall was conducted as a comprehensive study of the wall’s coupled nonlinear shear-flexure behavior under cyclic loading. The experimental results show that the RC wall failed in flexure mechanism, indicated by crushing of the flexural compression zone, and followed by immediate shear failure, notified by the occurrence of web crushing. In addition to the experiment, an analytical model using SFI-MVLEM element in OpenSees software was performed to verify the experimental results. The analytical results show that the model is able to simulate reasonably well the coupled nonlinear shear-flexure behavior of the RC wall subjected to cyclic loading.